1991
DOI: 10.2337/diacare.14.7.593
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Temporary and Permanent Disability Induced by Diabetes

Abstract: These results suggest that diabetic individuals without complications incur few additional costs compared with nondiabetic individuals. However, once complications appear, the indirect costs are very high, suggesting that secondary preventions of the diabetic complications might be an optimal approach for reducing the health-care burden of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Similar findings were reported other researchers in university employees in Argentina during 1984–1986, who reported retinal lesions as the most frequent cause of diabetes-induced disability and average work production loss per patient of 11 years [21]. …”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported other researchers in university employees in Argentina during 1984–1986, who reported retinal lesions as the most frequent cause of diabetes-induced disability and average work production loss per patient of 11 years [21]. …”
Section: Discussionsupporting
confidence: 90%
“…1 Previous work has shown that unemployment is a particular problem for people with diabetes, 2,3 and in terms of health and social outcomes, this may have serious consequences. 4,5 Unemployment does not only mean loss of income but can also result in loss of social status for individuals, can affect personal attachments, and is associated with other factors such as poor diet and housing. 6 It has also been demonstrated that unemployment is a good marker of both material and social deprivation and is highly correlated with hospital admission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in diabetes control has the potential to reduce direct costs involved in the treatment of complications. [21] Strict glycemic and blood pressure control can reduce the incidence and slow the progression of DN. [22] Improvement in diabetes control, early diagnosis of DN, and treatment has the potential to reduce the direct cost involved in treatment of DN.…”
Section: Discussionmentioning
confidence: 99%